Proximate Analysis of Milk-Based Jelly Candy with Different Bee Pollen Concentrations - Amertaningtyas, Dedes; Amalia, Alvina Wahyu; Evanuarini, Herly; Susilo, Agus; Jaya, Firman; Widati, Aris Sri (CV. Komunitas Dunia Peternakan, 2025)
This study aimed to evaluate the effect of bee pollen addition on the chemical composition of cow’s milk–based jelly candy. Bee pollen is a natural product rich in proteins, minerals, and bioactive compounds, which may enhance the nutritional value of food products. The research was conducted at the Dairy Technology Laboratory, Department of Animal Product Technology, Faculty of Animal Science, Universitas Brawijaya, from June to August 2025. The research method used was a laboratory experiment using Complete Randomized Design (CRD) ANOVA with 4 treatments and 4 replications. If different results were obtaindes between treatments, Duncan’s Multiple Range Test (DMRT) was continued. Four treatments were applied: T0 (control, without bee pollen), T1 (6%), T2 (12%), and T3 (19%). The results demonstrated that bee pollen supplementation had a highly significant effect (P<0.01) on the protein content (Kjeldahl method), moisture content (Gravimetri method), ash content (Dry Ashing method), and carbohydrate content (By Different method), but showed no significant effect (P>0.05) on fat content (Soxhlet method). Protein content increased from 16.83% to 19.30%, moisture content increased from 29.56% to 34.30%, while ash content exhibited a fluctuating trend. Conversely, carbohydrate content decreased from 52.90% to 45.19%. Overall, the addition of bee pollen improved the nutritional quality and functional potential of milk-based jelly candy, particularly as a natural source of protein and minerals.